THE DRILLING METHOD TO ENHANCE STUDENTS’ PUBLIC SPEAKING AT TAHFIDZ TAKHASSUS DAARUL QUR’AN ISLAMIC BOARDING SCHOOL PALEMBANG - Lutfiyatun, Eka; Shahab, Aisyah; Mulyadi, Ahmad Iman; Kurniati, Depi (Department of English Education, Universitas Panca Sakti Bekasi, 2023)
Indonesia is preparing to enter the era of Society 5.0 where all aspects of life are interconnected without space and time limitations. Students in Islamic boarding schools must also have the competence to communicate, to think critically, and to collaborate on projects. It is important for the younger generation to improve their public speaking competence so that they can express their critical and creative thoughts in front of others. This study is a descriptive qualitative study and the data are collected by observations. This study aims to describing how to train students’ public speaking skill through drilling method. The samples as well as subjects of this study were 28 students. Public speaking training was conducted for a month using the drilling method at the Tahfidz Takhasus Daarul Qur'an Islamic Boarding School Palembang. The drill method was carried out in seven steps namely association, objectives and core material delivery, motivation, practices, demonstration, evaluation, and program follow-up. The training was carried out by introducing the material through lectures and discussions, and was continued with the drilling method to train the students' rhetorical or speech competence in public. Students demonstrated public speaking in English, Arabic and Indonesian. The advice given to the training participants is to maximize training in public speaking, especially making speeches in various languages so that they can be used when engaging in society.Indonesia is preparing to enter the era of Society 5.0 where all aspects of life are interconnected without space and time limitations. Students in Islamic boarding schools must also have the competence to communicate, to think critically, and to collaborate on projects. It is important for the younger generation to improve their public speaking competence so that they can express their critical and creative thoughts in front of others. This study is a descriptive qualitative study and the data are collected by observations. This study aims to describing how to train students’ public speaking skill through drilling method. The samples as well as subjects of this study were 28 students. Public speaking training was conducted for a month using the drilling method at the Tahfidz Takhasus Daarul Qur'an Islamic Boarding School Palembang. The drill method was carried out in seven steps namely association, objectives and core material delivery, motivation, practices, demonstration, evaluation, and program follow-up. The training was carried out by introducing the material through lectures and discussions, and was continued with the drilling method to train the students' rhetorical or speech competence in public. Students demonstrated public speaking in English, Arabic and Indonesian. The advice given to the training participants is to maximize training in public speaking, especially making speeches in various languages so that they can be used when engaging in society.